Pemberdayaan Santriwati IMBS Miftahul Ulum Pekajangan dalam Mengolah Kunyit untuk Kesehatan Reproduksi dan Penguatan Karakter Mandiri Berbasis Nilai-Nilai Islam - Fuad, Asfal; Widiastuti, Windha; Wirotomo, Tri Sakti; Setianto, Gigih (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Reproductive health is an essential aspect of maintaining the quality of life and well-being among young generations, particularly female students in Islamic boarding schools (santriwati). This Community Service Program (PKM) aims to enhance reproductive health literacy based on Islamic herbal knowledge, develop practical skills in processing turmeric (Curcuma longa L.) as a natural remedy for menstrual pain (dysmenorrhea), and foster independent and religious character formation rooted in Islamic values. This study employed a field research method with a participatory approach, involving 30 female students aged 15–20 years from IMBS Miftahul Ulum Islamic Boarding School, Pekajangan. Data were collected through observation, interviews, documentation, and pre-test–post-test assessments to evaluate changes in knowledge, skills, and attitudes. The results indicate a significant improvement in students’ literacy regarding turmeric’s bioactive compounds and their benefits for reproductive health (from 27% to 80%), skills in processing fresh turmeric slices into herbal beverages (from 23% to 83%), and integration of Islamic values in health awareness (from 30% to 87%). Furthermore, 90% of the participants reported that drinking turmeric infusion effectively helped reduce menstrual pain while strengthening their spiritual awareness that maintaining health is an act of worship and part of the maqashid al-syari‘ah principle of hifdz an-nafs (preserving life). This program demonstrates that the integration of modern health science, traditional herbal wisdom, and Islamic values is effective in strengthening students’ independence, self-awareness, and sustainable healthy behavior. The PKM model can be replicated in other Islamic boarding schools as a holistic health education strategy grounded in Islamic principles, harmoniously combining science, spirituality, and practical skills.